Collaboration as Effective Music Professional Development: Success Stories From the Field. (October 2014) - Stanley, Ann Marie; Snell, Alden; Edgar, Scott
Collaborative professional development (PD) efforts are increasingly popular and successful across the United States. In this article, we highlight the voice of the teacher in brief descriptions of PD efforts that support collaboration as a key component of meaningful music teacher PD. To draw a vivid picture of the potential and possibilities in models of music teacher collaborative PD, we connect eight practicing teachers' positive PD experiences to recommendations from recent research findings. We also make suggestions for music teacher educators about the implications of these findings about the establishment of a disposition in preservice teachers toward valuing collaborative development.